Model based on fuzzy predicates for assessment of groundwater pollution vulnerability / Modelo basado en predicados difusos para la evaluación de la vulnerabilidad a la contaminación del agua subterránea - Lima, María Lourdes; Massone, Héctor; Barilari, Agustina; Albornoz, Daniel; Meschino, Gustavo (Tecnología y ciencias del agua, 2020)
Groundwater plays a substantial role in resource supply, in ecosystem functioning and human well-being. The aim of this study is develop a tool to assess the groundwater vulnerability through of fuzzy predicates in an area in the Pampas Plain in Argentina. Knowledge is represented as a main fuzzy predicate whose degree of truth is computed by means of numerical variables to determine a degree of groundwater vulnerability. Thematic Fuzzy System (TFS) software has been developed using MATLABÂ® to design and optimize a fuzzy predicates based model. The results in the final fuzzy map identified the middle and lower basin as areas with high and very high truth values for the main predicate "Groundwater is vulnerableâ€, thus, these sectors were defined as the main areas of greatest vulnerability. This study showed that fuzzy models are more efficient computer-base tools for decision-makers in the water resources management due to high discrimination of the territory, producing successful results using fewer variables than other ordinary approaches.